Groundwater characteristics of the Saga Plain, Japan - Wang, Lin; Iwao, Yushiro (Journal of Nepal Geological Society, 2000)
The Saga Plain is located in the west of Kyushu Island, Japan. The area is seriously affected by overdraft of groundwater. Land subsidence has been evident since 1957, and it was quite significant in 1960. The groundwater head varies seasonally depending on discharge and precipitation. According to the geological properties of the Saga Plain, a single layer two-dimensional plane model was adopted to simulate the seasonal fluctuation of the groundwater head. Based on the Darcy's Law and continuity principle, the following differential equation was used to describe the groundwater flow: (Tꝺ2h)/ ꝺx2 + (Tꝺ2h)/ ꝺy2 = Sꝺh/ꝺt + Q(x,y,t) where, T is the transmissivity of aquifer; S is the storage coefficient; Q is the net recharge; and h is the groundwater head. By comparing the pattern of the Hexa diagram in different areas and different aquifers, it was found that saltwater intrusion occurred in the Saga Plain due to over-pumping. Water quality and quantity are affected not only by the recharge and soil utilisation but also by the surrounding geological conditions. Tritium concentration analysis was used for estimating the age of groundwater in the Saga Plain. The Saga Plain is divided into the Saga District and Shiroyishi District. In the Saga District, the groundwater showed a young age in the shallow wells of inland as well as coastal areas. The young age in the inland areas was attributed to the recharge of groundwater from the northern mountains. For the coastal areas, it was thought as the effect of saltwater intrusion from the Ariake Sea. Meanwhile, measurements showed that the groundwater in deep aquifers was of old age in the Saga District. Those results were also supported by the chemical analyses of the components of groundwater in the Saga Plain. In the Shiroyishi District, the old groundwater was encountered both in deep and shallow aquifers. The analyses of chemical components showed that the groundwater is affected mainly by the fossil water in the Shiroyishi District.